Kaum dan Nagari: Eksistensi Kaum dalam Pembangunan di Nagari Pasia Laweh Kecamatan Palupuah Kabupaten Agam - Bestari, Ibnu Chalid; Putera, Roni Ekha; Aromatica, Desna (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Kaum is one of three forms of kinship groups in Minangkabau society. Kaum is a collection of several paruik, and suku is a collection of several kaum and nagari consists of at least four suku. The existence of paruik, kaum and suku in the lives of nagari people is still felt to this day. The existence of this group is still felt in Nagari Pasia Laweh, including in development activities. This research will look further at the existence of groups in development in Nagari Pasia Laweh, Palupuah District, Agam Regency. The research method used is qualitative with descriptive analysis. Data collection techniques use interviews and documentation. The results of the research show that the people of Nagari Pasia Laweh still live in groups called tribes. People are the most important element in development in Nagari Pasia Laweh, and every stage of development is carried out by people. sahino samalu motto makes all people want to be actively involved in development activities, in order to advance the nagari and meet the needs of the people.